EVALUASI KEBERGUNAAN PLATFORM PEMBELAJARAN DIGITAL SEKOLAH AL-FITYAN MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Magfirah, Magfirah; Hayati, Lilis Nur; Darwis, Herdianti (IDEALIS : InDonEsiA journaL Information System, 2024)
LMS AFDAL is a learning system that is applied within the scope of SMPIT Al-Fityan School Gowa. This LMS is used to facilitate modern learning. Evaluation of the AFDAL LMS is the first step to assess whether the LMS is well received or not by users. There are many approaches that can be taken in evaluating, one of which is usability evaluation. This study aims to determine the level of usability based on the System Usability Scale method with five variables, namely learnability, efficiency, memorability, errors, and satisfaction with 10 statements as a measure of quality in terms of the usability of the LMS. This research was conducted by distributing questionnaires using google form to 306 respondents consisting of teachers and students via whatsapp. Data processing uses IBM SPSS V26 and Microsoft Excel 2019. The results of the validity and reliability tests are declared valid and reliable. The results of the SUS test show that the final SUS value of 306 respondents' responses is 64.6, according to the rules of SUS interpretation that the score is 64.6 for the Acceptability Ranges level, namely Marginal (quite acceptable), the Grade Scale results in terms of user acceptance levels are included in the C- level, and Adjectives The rating is included in the OK category. These results indicate that the AFDAL LMS is quite accepted by its users, but this figure is quite low so that some improvements are needed to make it even better.